Kebijakan Refocusing Anggaran dan Strategi Di Masa Pandemi Covid-19 - Giovani Rizki Dhia Aldila; Sri Dwi Estiningrum (Politeknik Ganesha Medan, 2022)
The existence of Covid-19 in the government sector led to the issuance of Presidential Instruction Number 4 of 2020 which contains a budget priority policy for handling Covid-19, namely refocusing the budget for regional work units (SKPD). In making policy, a leader needs to pay attention to the situation, condition, and observe when carrying out the strategy to be taken, of course by taking into account the inhibiting factors and supporting factors, and communication. In taking action decisions, it is necessary to look at the positive and negative sides and think about the consequences of making a decision. With this regulation, it is hoped that the budget can be allocated optimally through several strategies. From the strategies carried out, among others, delaying programs and activities, reducing this spending budget also has an impact on UMKM actors because not all can participate due to target restrictions, and training is postponed. This study aims to see and examine the steps taken in optimizing the budget. This research method is qualitative, data collection is done by triangulation (combined observation, interviews, documentation). This research begins by conducting a survey to the research location, then collecting data which includes observation, interviews, documentation of the results of data collection, then analyzes the data by means of identification. Based on the results of observations and interviews, it is known that the strategies carried out include budget revisions, program delays or budget absorption activities that have been quite successful, as can be seen through the Government Performance Report (LKJIP) 2020-2021.